FERDYNAND BALYTSKYI (1877–1952) FROM HALYCH: TEACHER, MILITARY OFFICER, AND PUBLIC FIGURE - CHEMERYNSKYI, Andrii (Halych. Scientific work collection, 2019)
The article describes the way of life and socio-political activity of a teacher, a military officer, a sotnyk of UGA Ferdinand Balytsky (1877–1952). On the basis of source materials, his participation in hostilities during the First World War and in the hands of the Ukrainian Galician Army was presented; active activities among Ukrainian prisoners of war in concentration camps in Tukholia and Josefow; pedagogical work in Mariyampol, Uzhgorod and Halych.